2017
DOI: 10.31887/dcns.2017.19.2/bbandelow
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of anxiety disorders

Abstract: Anxiety disorders (generalized anxiety disorder, panic disorder/agoraphobia, social anxiety disorder, and others) are the most prevalent psychiatric disorders, and are associated with a high burden of illness. Anxiety disorders are often underrecognized and undertreated in primary care. Treatment is indicated when a patient shows marked distress or suffers from complications resulting from the disorder. The treatment recommendations given in this article are based on guidelines, meta-analyses, and systematic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
272
0
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 514 publications
(353 citation statements)
references
References 104 publications
2
272
0
16
Order By: Relevance
“…As psychiatric disorders are associated with an important social stigma ( Rössler, 2016 ), previous research may have been biased and it is possible that anxiety may have been underreported. Besides, anxiety symptoms and anxiety disorders are distinct entities, and anxiety symptoms frequently correspond to an adaptive and physiological response to a stressor requiring little, if any, specific treatment and management ( Bandelow et al, 2017 ; Steimer, 2002 ). In this context, further data on the impact of the COVID-19 pandemic on the diagnosis of anxiety disorder are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…As psychiatric disorders are associated with an important social stigma ( Rössler, 2016 ), previous research may have been biased and it is possible that anxiety may have been underreported. Besides, anxiety symptoms and anxiety disorders are distinct entities, and anxiety symptoms frequently correspond to an adaptive and physiological response to a stressor requiring little, if any, specific treatment and management ( Bandelow et al, 2017 ; Steimer, 2002 ). In this context, further data on the impact of the COVID-19 pandemic on the diagnosis of anxiety disorder are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggests that elevated inflammation contributes to the pathophysiology of anxiety disorders, such as post-traumatic stress disorder (PTSD) [ 173 ], and that anti-inflammatory drugs might be a new treatment strategy for PTSD [ 188 ]. Various clinically used anxiolytics have other actions and target redox-inflammatory processes indirectly, such as agomelatine [ 189 ] and the SSRIs [ 190 ]. These drugs are approved for the management of chronic anxiety-related disorders [ 190 ].…”
Section: The Association Between Stress Inflammation and Treatment Rmentioning
confidence: 99%
“…Various clinically used anxiolytics have other actions and target redox-inflammatory processes indirectly, such as agomelatine [ 189 ] and the SSRIs [ 190 ]. These drugs are approved for the management of chronic anxiety-related disorders [ 190 ]. However, given the central role that GABA plays in anxiety-related disorders [ 191 ].…”
Section: The Association Between Stress Inflammation and Treatment Rmentioning
confidence: 99%
“…In clinics, most patients with anxiety disorders who seek help are suffering from generalized anxiety disorder (GAD), pathological demand avoidance (PDA), and seasonal affective disorder (SAD) 10 . Their treatment can be performed most of the time in an outpatient setting 11 . Many studies have shown the efficacy of medications for GAD, PDA and SAD, but there are very few treatment studies for specific phobias 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Supportive talks and attention to the emotional issues of anxiety patients are important in the treatment of these patients. Psychoeducation and provision of information on the physiology of symptoms of anxiety and available treatment options can be helpful 11 . Cognitive behavioral therapy (CBT) as a practical and structured form of psychotherapy has been shown to be effective in the treatment of anxiety disorders [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%